Inhibition of gelatinase activity in pancreatic islet graft reduces cellular inflammation and restores islet function - Lingwal, Neelam; Justus Liebig University Giessen (My University, 2012)
Islet transplantation provides an approach to compensate for loss of insulin producing cells in patients with type 1 diabetes. However, the intraportal route of transplantation is associated with instant inflammatory reactions against the graft and subsequent islet destruction as well. While matrix metalloproteases (MMP) 2 and 9 are involved both in remodelling of extracellular matrix and leukocyte migration, their influence on the outcome of islet transplantation has not been characterized.Analysis of MMP-2 and MMP-9 in islet cells by zymography, gelatin dequenching assays, and western blot showed that in normal state, islets were expressing less MMP but treatment with inflammatory cytokines increased MMP-2 and MMP-9 secretions from them. However, islet transplantation in mice liver showed less MMP activity in the transplanted islet and more with the recipient liver. We observed comparable MMP-2 mRNA expressions in control and transplanted groups of mice, whereas MMP-9 mRNA and protein expression levels increased after islet transplantation. Immunostaining for CD11b (Mac-1) expressing leukocytes (macrophage, neutrophils) and Ly6G (neutrophils) revealed substantially reduced inflammatory cell migration into islet-transplanted liver in MMP-9-knockout (KO) recipients. Moreover, gelatinase inhibition resulted in a significant increase in the insulin content of transplanted pancreatic islets and reduced macrophage and neutrophil influx as compared to the control group. These results indicate that increase of MMP-9 expression and activity after islet transplantation is directly related to enhanced leukocyte migration and that early islet graft survival can be improved by inhibiting MMP-9 (gelatinase B) activity.

Die Inselzelltransplantation bietet einen Ansatz in der Therapie von Patienten mit Typ 1 Diabetes, um den Verlust insulinproduzierender Zellen zu kompensieren. Allerdings ist die Transplantation auf dem Wege der intraportalen Applizierung mit einer sofortigen Entzündungsreaktion gegen das Transplantat und nachfolgend mit einer Zerstörung der Inselzellen assoziiert. Obwohl die Matrix-Metalloproteasen (MMP) 2 und 9 sowohl an der Umbildung von extrazellulärer Matrix, als auch an der Leukozyten-Migration beteiligt sind, wurde ihr Einfluss auf den Ausgang von Inselzelltransplantationen bisher nicht beschrieben.Die Untersuchung der MMP-2 und MMP-9 in Inselzellen mittels Zymographie, Gelatine Dequenching Assay und Western Blot zeigte zum einen, dass Inselzellen unter Normalbedingungen wenig MMP exprimieren, zum anderen aber, dass sie unter Behandlung mit entzündungsfördernden Zytokinen mehr MMP-2 und MMP-9 sezernieren. Die gemessene MMP-Aktivität war jedoch nach der Transplantation von Inselzellen in die Leber von Mäusen in den transplantierten Inseln niedriger und in der Empfängerleber höher. Wir fanden vergleichbare Expressionen von MMP-2-mRNA in der Kontrollgruppe und in der Gruppe der transplantierten Mäuse, wohingegen die Expressionslevel von MMP-9-mRNA und -Protein in Inseltransplantaten höher lagen. Die immunhistologische Färbung von CD11b-(Mac-1-) exprimierenden Leukozyten (Makrophagen, Neutrophile) und Ly6G (Neutrophile) offenbarte eine erheblich reduzierte Migration von Entzündungszellen in die Leber von MMP-9-knockout (KO) Empfängertieren, in die die Inseln transplantiert wurden. Zudem führte die Hemmung der Gelatinase zu einer signifikanten Zunahme des Insulingehaltes in transplantierten Inseln aus dem Pankreas und zu einer Abnahme der Makrophagen- und Neutrophileninfiltration im Vergleich zur Kontrollgruppe.Diese Ergebnisse deuten darauf hin, dass eine Zunahme der MMP-9-Expression und -Aktivität nach einer Inselzelltransplantation direkt im Zusammenhang mit einer gesteigerten Leukozytenmigration steht und, dass das frühe Überleben der Transplantate durch die Hemmung der MMP-9- (Gelatinase B) Aktivität gefördert werden kann.
Keywords: ddc:610